Flower, inverted! - Jutta, Mariam (University Putra Malaysia, 2012)
A fig is actually an inverted receptacle, known as a synconium that encloses three types of simple male, female and sterile gall flowers, and later the seeds. Male flowers carry pollen, female flowers have long styles for easy pollination, while stalked gall flowers feed the larvae of fig wasps. Fig and wasp form one of the most extraordinary plant-animal associations we know with each species of fig pollinated by only one type of wasp.